Early Active Exercise Improves MDA, SOD, and GSH Levels without Memory or NO Changes in Wistar Rats - Muhammad Hafiz Zuhdi Fairof; Arimi Fitri Mat Ludin; Nur Diyana Anas; Ainaa Husna; Ahmad Muhaimin Che Hasan; Amirul Hafiz Ahmad Abdullah; Farah Wahida Ibrahim; Adriyan Pramono; Nor Fadilah Rajab (Indonesian Biomedical Journal)
BACKGROUND: Circadian rhythms regulate various physiological processes, including responses to exercise. However, the effects of exercise timing on cognitive function and oxidative stress remain unclear. One key factor in oxidative stress is nitric oxide (NO), an enzyme complex that produces reactive oxygen species (ROS) as part of normal cellular signaling. Excessive NO activity can disrupt redox balance and contribute to neuronal damage. An imbalance favoring oxidative stress can impair memory and learning, while a higher antioxidant capacity supports brain health and cognitive performance. This study was performed to investigate whether early active and late active aerobic exercise differentially impact cognitive function and oxidative stress biomarkers in Wistar rats.